Playing the Game: An Exploration of the Lived Experience of Australian Elite Level Athletes, with a Focus on their Mental Health and Wellbeing - Dessauvagie, Jemma Bonnie (Curtin University, 2018)
This research adopted an ecological orientation to extend understandings of the impact of extrinsic factors on athlete wellbeing. Athletes and support staff were engaged in semi-structured interviews analysed via causal layered analysis. Findings provided a holistic account of athletes’ lived experiences which reflected a “dark side” of elite and professional sport. Key messages revealed a dissonance between ‘the athlete’ and ‘a human’ and, spoke to athletes’ experiencing performance pressure beyond the competitive domain.